KONTRIBUSI PEMBELAJARAN BAHASA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK - Ambarwati, Erna (El-Hamra, 2019)
Speaking of you, then I will know who you are". This statement shows that language is a personal reflection of a person. A person's character, character or personality can be identified from the language he uses. The use of soft, polite, polite, systematic, orderly, clear, and straightforward language reflects the personality of educated and virtuous speakers. On the contrary, through the use of language that is sarcasm, blasphemy, cursing, slandering, discrediting, provoking, mocking, or harassing, it will portray an uneducated and unkind person. So that is exactly the sound of the proverb, "Language shows the nation". The importance of the role of language in the life of the community, nation, and state, so a policy that has implications for language development and learning in the community and educational institutions is needed. One form of guidance that is considered the most strategic in the world of education is Indonesian language learning in schools. The role of the teacher in efforts to guide and learn languages plays a very important role. The teacher becomes a personal figure who becomes a role model in language skills. The teacher is responsible for the success of language learning. In order for the purpose of language learning to be realized, namely 'students are able to communicate well and correctly', the teacher's knowledge and understanding is needed in relation to language learning strategies that refer to the basic principles of language learning, namely contextual, functional, integrative, and appreciative principles. three language learning approaches, namely a comprehensive language learning approach (whole language), process approach, and communicative approach.Key Words: language learning, character formation